Optimizing the Role of School Health Units (UKS) for Early Detection of Non-Communicable Diseases (NCDs) in Adolescents at School - Nurhayati, Nice; Putri, Anggelin Meike Qurnia; Nurlita, Yolanda Syifa; Agustin, Atin (BKM Public Health and Community Medicine, 2024)
Background: Non-communicable diseases (NCDs) are primarily caused by lifestyle and behavioral factors and contribute significantly to the prevalence of more severe health issues. Early intervention through screening is crucial to identify individuals at risk and manage these diseases before they escalate. School Health Units (UKS) embody the principles of health education, health services, and promoting a healthy school environment, which can significantly enhance student health and create a conducive learning environment. This study aims to promote the role of UKS in the routine early detection of NCDs among school adolescents. Methods: This study reviews existing literature and examines the current trends of NCDs in Indonesian adolescents. It highlights the discrepancy between the intended comprehensive role of UKS and its current curative-focused practice. The study proposes the implementation of Integrated Development Posts (POSBINDU) within schools as a strategic measure for early screening and prevention of NCDs. Results: The findings indicate a rising trend of NCDs shifting from the elderly to adults and adolescents in Indonesia. Research shows that adolescents are increasingly affected by NCDs, with prevalence rates rising over the past decades. Most adolescents in Indonesia attend secondary schools, spending a significant portion of their day on school premises. However, the current role of UKS is limited to providing curative health services, which is misaligned with the comprehensive health promotion values of UKS. Conclusion: Optimizing the role of UKS by integrating POSBINDU can provide an essential early screening tool for detecting NCDs among school adolescents. This integration can facilitate immediate intervention by healthcare centers and hospitals, thereby enhancing the overall health management system for adolescents.